Selective Sharing of Load Current Components Among Parallel Power Electronic Interfaces in Three-phase Four-wire Stand-alone Microgrid - Mortezaei, Ali; Simões, Marcelo Godoy; Marafão, Fernando Pinhabel [UNESP]; Guerrero, Josep M.; Durra, Ahmed Al; Busarello, Tiago Davi Curi (Taylor & Francis, 2017)
This paper investigates selective sharing of load current components among the parallel operation of distributed generators (DGs) in three-phase four-wire stand-alone microgrids. The proposed control method is based on master-slave operation of DGs, and the goal of selective sharing of load current components is to have DGs located in close proximity of the load operating in slave mode, in order to inject their available energy and also compensate the non-active load current components, while the distant DGs might operate in master mode to share the remaining load autonomously. Droop control is employed due to impracticality of communication at remote nodes, and resistive line impedance compensation is adopted to decouple active and reactive power controllers and ensure proper active power sharing among master DGs, irrespective of the mitigation of non-active current components by the slave inverters. The sharing factors for each current component are determined by a higher level control. The Conservative Power Theory (CPT) decompositions provide decoupled power and current references for the inverters, resulting in a selective sharing strategy. The principles supporting the developed control strategy are discussed, and the effectiveness of the control is demonstrated through computational simulations using PSIM software.
Keywords: active power filter; conservative power theory; distributed generation; four-leg inverter; load current sharing; microgrids; power quality improvement